A distributional analysis of social group inequality in rural India - Mehtabul Azam (Institute for the Study of Labor (IZA), 2009)
This paper examines the differences in welfare, as measured by per capita expenditure (PCE), between social groups in rural India across the entire welfare distribution. The paper establishes that the disadvantage suffered by two historically disadvantaged groups - Scheduled Castes (SCs) and Scheduled Tribes (STs) - is underestimated when the comparison group is Non-SCs/STs rather than general category (mostly higher castes). The ST households are the most disadvantaged followed by the SC and the Other Backward Caste households with respect to general category households, and the disadvantage exists across the entire distribution. Better covariates and better returns to those covariates contribute to the advantage of the general category households. The findings suggest that the policies to raise the human capital and strengthening the other productive assets of the SC and the ST households must remain a focus of attention besides promoting a more active labor market in rural India.
urn:nbn:de:101:1-20090210121
Keywords: C15; D63; O53; 330; India; social groups; inequality; quantile regression decomposition; Soziale Schicht; Soziale Ungleichheit; Sozialpolitik; Schätzung; Ländlicher Raum; Indien